2003
DOI: 10.1614/0043-1745(2003)051[0569:wsrssa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Weed seed rain, soil seedbanks, and seedling recruitment in no-tillage crop rotations

Abstract: Relationships among weed seed rain, soil seedbank, and seedling recruitment in no-tillage systems were studied from July 1993 to May 1996. Multiple regression analysis indicated that seedling recruitment of only six of the 25 weed species present was correlated with seed rain samples from the previous autumn, spring soil seedbank samples, or a combination of the two. However, seedling recruitment of the dominant annual grasses (yellow foxtail, giant foxtail, and fall panicum in Field 1–1994, Field 2–1995, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 34 publications
3
30
1
1
Order By: Relevance
“…The results obtained in field crops (12.2 -35.8%) were consistent with what was found previously for the species in similar habitat types, 6.8-38.2% (Forcella et al, 1992), 42% (Rothrock et al, 1993) and 15 -39% (Webster et al, 2003). The results obtained in field crops (12.2 -35.8%) were consistent with what was found previously for the species in similar habitat types, 6.8-38.2% (Forcella et al, 1992), 42% (Rothrock et al, 1993) and 15 -39% (Webster et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results obtained in field crops (12.2 -35.8%) were consistent with what was found previously for the species in similar habitat types, 6.8-38.2% (Forcella et al, 1992), 42% (Rothrock et al, 1993) and 15 -39% (Webster et al, 2003). The results obtained in field crops (12.2 -35.8%) were consistent with what was found previously for the species in similar habitat types, 6.8-38.2% (Forcella et al, 1992), 42% (Rothrock et al, 1993) and 15 -39% (Webster et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…A. artemisiifolia forms a persistent soil seed bank (Thompson et al, 1997). The overall seed-bank densities of A. artemisiifolia in field-crop habitats have been analysed previously (Raynal and Bazzaz, 1973;Bigwood and Inouye, 1988;Gross, 1990;Rothrock et al, 1993;Webster et al, 2003). The seeds that do not germinate in spring re-enter dormancy due to secondary dormancy mechanisms (Bazzaz, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…The seedbank study revealed a significant increase in the number of weed seeds and species, mainly of annual grasses such as Digitaria sanguinalis and Panicum dichotomiflorum, in CoT and NT (Menalled et al, 2001). Positive relationship was noted among weed seed rain (16-77%), seedbank (12-78%), and seedling recruitment (32% of the emerged seedlings) in NT for the annual grasses viz., yellow foxtail, giant foxtail, and fall panicum (Webster et al, 2003). Obviously weed species assembly in NT and CoT had assorted weed species, confirming the ability of seedbanks to buffer disturbances across a variety of cropping systems (Legere et al, 2005a).…”
Section: No Tillagementioning
confidence: 72%
“…The natural variability of weed emergence is confounded by difficulties in studying the seed bank, as discussed above. Within a single seed bank quantification study, coefficients of variation for germination typically exceed 50% . Greenhouse studies of seedling emergence have been somewhat more accurate than field studies, however the artificial nature of the greenhouse challenges study of seed traits such as dormancy or community processes such as self‐thinning .…”
Section: Exiting the Weed Seed Bankmentioning
confidence: 99%